Structural dynamics of the E6AP/UBE3A-E6-p53 enzyme-substrate complex - Carolin Sailer (Nature Portfolio, 2018)
Oncoprotein E6 facilitates the E6AP-catalyzed ubiquitination of p53. Here, the authors study the structural basis of this process by qualitative and quantitative cross-linking mass spectrometry, providing insights into E6AP-E6-p53 complex assembly and the conformational dynamics that enable p53 ubiquitination.